Algumas contribuições da literatura infantil na educação escolar: o caso do livro “a pontinha menor-zinha do enfeitinho do fim do cabo de uma colherzinha de café”. - Santos, Maria de Fátima Laurindo dos (Universidade Federal do Tocantins, 2023)
Children's literature is an activity that pleases children, allowing them to develop fully. Literature is essential in childhood, so it is necessary that the school offers activities for the full development of the student, it is very important for the development of oral language, it allows learning to take place in a broader way, which precedes and underlies that of written language. Literature is an important didactic resource with great application and motivation to train future readers. The reason for choosing this theme for this work was to check if, in fact, the literature works as a contribution to child development, favoring the individual growth of the child and helping them to internalize the knowledge and social norms, which are essential in the beginning of schooling. In this line of reflection, we intend to go deeper into the importance of literature for children. The relevance of this theme justifies its choice for this study, because children's literature are pleasurable actions that populate the children's world.